Taraxacum sinicum Kitag. (Binpu-3) root extract inhibits tumor invasion via Notch signaling in Drosophila and human breast cancer MDA-MB-231 cells - Wu, Jiawei; Zhang, Jianbo; Shu, Wanyu; Feng, Wei; Meng, Ran; Kong, Lingyu; Cao, Huijuan; Jiang, Chunhua; Wang, Sitong; Wu, Fanwu; Wu, Chenxi; Wang, Xiuping (Frontiers in Pharmacology, 2025)
Metastasis is the primary cause of death in patients with malignant tumors. Therefore, effectively controlling or reversing tumor cell growth and metastasis is crucial for treating malignant tumors. In this study, we investigated the effects and underlying mechanisms of Binpu-3 (a strain of Taraxacum sinicum Kitag., which was cultivated in slightly saline-alkali soil) on tumor invasion both in Drosophila and human breast cancer cells. High-performance liquid chromatography (HPLC) analysis revealed that caftaric, chlorogenic, caffeic, and cichoric acids in the Binpu-3 leaves and roots were significantly higher than those in the wild-type Handan strain. Binpu-3 root extract (Binpu-3RE) suppressed the invasion rate of tumor cells at 25.00 mg/mL in the Drosophila eyeful model, whereas Binpu-3 leaf extract had no obvious effect on tumor metastasis. Accordingly, we found that caffeic acid, quercetin, apigenin, and taraxasterol content in Binpu-3 roots was significantly higher than that in the leaves. In addition, ultra performance liquid chromatography-high resolution mass spectrometry (UPLC-HRMS) analysis revealed that Binpu-3RE contained various constituents, including pantothenate (0.1%), butein (0.53%), chlorogenate (0.78%), chicoric acid (1.96%), azelaic acid (0.23%), and [6]-gingerol (0.13%). In vivo, Binpu-3RE impeded ptc>scrib-IR triggered cell migration in Drosophila at an appropriate concentration, and 25.00 mg/mL was selected as the best dose to carry out follow-up mechanistic research. This dose of Binpu-3RE reduced the mRNA levels of Notch pathway key genes Delta, Serrate, Notch, Su(H), and En(spl), the expression levels of NRE-GFP (Notch activity reporter), β-integrin, and metalloproteinase-1 (MMP1) in Drosophila. Cell viability, wound healing, transwell, and Western blotting assays data implied that Binpu-3RE reduced cell growth, migration, invasion, and the expression of Notch1, Jagged1, and HES1 in human breast cancer MDA-MB-231 cells. In summary, the saline-alkali tolerant dandelion Binpu-3 used in this study was of excellent quality, and the root extract showed significant anti-tumor metastasis effects via reduction of Notch signal activity and the expression β-integrin and MMP1 proteins in Drosophila and breast cancer cells, providing a theoretical basis for the development and use of alkaline-soil dandelion herbs, and a therapeutic strategy for the clinical treatment of malignant breast cancer.